2020
DOI: 10.1103/physrevmaterials.4.084007
|View full text |Cite
|
Sign up to set email alerts
|

Large interfacial spin-orbit torques in layered antiferromagnetic insulator NiPS3 /ferromagnet bilayers

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…Another example of interfacial SOT with 2D magnets is given by the SOT results on bilayers of the 3D ferromagnet NiFe and the 2D AF insulator NiPS 3 . 449 As the large SOTs acting on NiFe include components of the different “damping-like” and “field-like” symmetries, they can be ascribed to interfacial SOT. The SOT increases below the Néel temperature of NiPS 3 (170 K), pointing out a possible relation with magnetic ordering.…”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 99%
“…Another example of interfacial SOT with 2D magnets is given by the SOT results on bilayers of the 3D ferromagnet NiFe and the 2D AF insulator NiPS 3 . 449 As the large SOTs acting on NiFe include components of the different “damping-like” and “field-like” symmetries, they can be ascribed to interfacial SOT. The SOT increases below the Néel temperature of NiPS 3 (170 K), pointing out a possible relation with magnetic ordering.…”
Section: Spintronics: From Fundamentals To Devicesmentioning
confidence: 99%
“…SOT effective fields per unit current density of FeRh derived from harmonic Hall voltage measurements as a function of the temperature T , including (a) damping-like effective field H DL and SOT efficiency ξ SOT and (b) field-like effective field ( H FL ). (c) Plot for various systems with a temperature-tunable SOT, the tunability of the SOT efficiency being defined as the relative change of ξ SOT per unit temperature change |Δξ SOT /Δ T | max (the subscript means the temperature range where the SOT efficiency exhibits the steepest change was considered for each system) against the maximum value of ξ SOT in the whole temperature range of tuning |ξ SOT | max . ,, …”
Section: Resultsmentioning
confidence: 99%
“…Heterostructures of MnPSe 3 and MoS 2 show a type-II band alignment, important for optics, and a stacking dependent lifting of spin and valley degeneracy in MnPSe 3 [57], potentially interesting for valleytronics applications [58,59]. Moreover, it has been shown that antiferromagnetic FePS 3 increases the coercive field and Curie temperature of the 2D itinerant ferromagnet Fe 3 GeTe 2 [60], while NiPS 3 can be important to tailor interfacial spin-orbit torques [61].…”
Section: Unlike Ferromagnets Antiferromagnetic Monolayersmentioning
confidence: 99%